O-specific polysaccharide structure isolated from the LPS of the Antarctic bacterium Pseudomonas ANT_J38B. (November 2020) - Di Guida, Rossella; Casillo, Angela; Corsaro, Maria Michela
Abstract: Pseudomonas ANT_J38B is a Gram-negative bacterium isolated from an Antarctic island. LPS was extracted using the phenol/chloroform/petroleum ether method. A mild acid hydrolysis followed by a gel filtration purification afforded the O-chain. The polysaccharide was characterized by means of chemical analyses and NMR spectroscopy. The O-chain displays a disaccharide repeating unit with the following backbone: →4)-α-l -Gul p NAc3OAcAN-(1 →3)-β-d -Qui p NAc-(1→ . Graphical abstract: Image 1 Highlights: The Antarctic bacterium Pseudomonas ANT_J38B produced a smooth-LPS. The O-specific polysaccharide from Pseudomonas ANT_J38B was extracted and purified. The OPS structure was completely characterized by 1D and 2D NMR spectroscopy. The OPS consists of a disaccharide repeating unit containing β-d -Qui2NAc and α-l -GulNAc3OAcAN.